Spatial Autocorrelation Between Poverty Factors and Exclusive Breastfeeding Intake with Stunting in West Java Province at 2018 - 2020 - Yuli Puspita Devi; Sofwatun Nida; Roma Yuliana; Rizna Notarianti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting is a condition of growth failure in toddlers that leads to reduced productivity and susceptibility to degenerative diseases. The prevalence of stunting in West Java Province was the highest on the island of Java in 2018-2020. The objective of this study was to analyze the distribution map and spatial autocorrelation for stunting prevalence in West Java Province, with considering the spatial effects. The present study employed an ecological design with a spatial approach. The research data was obtained from Open Data Jabar, which is freely accessible via the website. The analysis was conducted using GeoDa software. The results indicate an increase in the areas demonstrating spatial effects between stunting and breastfeeding each year (2018–2020). Concurrently, the spatial implications of poverty on stunting necessitate further examination in the western region of West Java Province, particularly in Sumedang, Tasikmalaya, and Indramayu.